Altered gut microbiome plays an important role in AKI to CKD transition in aged mice - Kim, Myung-Gyu; Cho, Won Yong; Chung, Suk Min; Choi, Young Eun; Fang, Yina; Park, Myeong Soo; Park, Sang Jun; Ko, Yoon Sook; Lee, Hee Young; Yang, Jihyun; Oh, Se Won; Jo, Sang-Kyung (Frontiers in Medicine, 2023)
This study investigated the role of renal-intestinal crosstalk in the transition from acute kidney injury (AKI) to chronic kidney disease (CKD) in elderly individuals. Using young and aged mice, we induced bilateral ischemia-reperfusion injury (IRI) and compared intestinal and kidney inflammation over 28 days. To determine the role of the microbiome in gutkidney crosstalk, we analyzed the microbiome of fecal samples of the young versus aged mice and examined the effects of probiotic supplementation. In the post-IRI recovery phase, prolonged intestinal and renal inflammation along with dysbiosis were evident in aged versus younger mice that was associated with severe renal dysfunction and fibrosis progression in aged mice. Probiotic supplementation with Bifidobacterium bifidum BGN4 and Bifidobacterium longum BORI alleviated intestinal inflammation but not intestinal leakage, characterized by decreased inflammatory cytokine levels and decreased infiltration of macrophages, neutrophils, and Th17 cells. This was associated with improved M1-dominant renal inflammation and ultimately improved renal function and fibrosis, suggesting that renal-intestinal crosstalk in aged mice contributes to the transition from AKI to CKD. Our study findings suggest that exacerbation of chronic inflammation through the gut-kidney axis might be an important mechanism in the transition from AKI to CKD in the elderly.